Controlled Initiation of Chromosomal Replication in Escherichia coli Requires Functional Hda Protein - Camara, Johanna Eltz (American Society for Microbiology, 2003)
Regulatory inactivation of DnaA helps ensure that the Escherichia coli chromosome is replicated only once per cell cycle, through accelerated hydrolysis of active replication initiator ATP-DnaA to inactive ADP-DnaA. Analysis of Δhda strains revealed that the regulatory inactivation of DnaA component Hda is necessary for maintaining controlled initiation but not for cell growth or viability.